A SHARED study-the benefits and costs of setting up a health research study involving lay co-researchers and how we overcame the challenges. Issue 1 (December 2016) - Mockford, Carole; Murray, Matt; Seers, Kate; Oyebode, Jan; Grant, Richard; Boex, Sue; Staniszewska, Sophie; Diment, Yvonne; Leach, Jim; Sharma, Uma; Clarke, Rosemary; Suleman, Rashida
Plain English summary In the United Kingdom (UK), official bodies such as the Department of Health and research funders such as the National Institute for Health Research support and encourage lay involvement in all stages of research studies. The SHARED study has had substantial patient and public involvement (PPI) from developing the idea to dissemination. The aim of the study has been to develop recommendations led by service users for health and social care professionals to use at hospital discharge and in care planning for people living with memory loss and their carers. This article is about how the study started and the benefits, costs and challenges we encountered as the lead and lay co-researchers. Once we were successful with the grant application, we had to recruit and train the lay co-researchers and obtain various approvals before we could start the project. We had various support from funders, the Research Ethics Committee, lay members of Alzheimer's Society and from the lay co-researchers. However, we encountered some challenges with paying the lay co-researchers and with getting the approval for the co-researchers to interview staff on NHS premises. The challenges were overcome eventually but some aspects of the study changed because of this. We suggest that some changes could be made to the research system which would lead to greater inclusion of the lay co-researchers in research studies and would make the process more straightforward for the research team. Abstract Background Involving patients and the public in all stages of research has been the focus of the SHARED study. Patient and public involvement (PPI) is an important strategic priority for the Department of Health and funders such as the National Institute for Health Research. The aim of this paper is to describe the benefits, challenges and costs involved in setting up the research study with lay members as part of the research team. The study focused on developing service user-led recommendations for people with memory loss and their carers, on discharge from acute hospital to the community. Methods This began with a discussion of an initial research idea with a lay group of carers and people living with dementia. Once funded, approval was sought from the Research Ethics Committee and NHS Trusts to conduct the research including the active involvement of lay co-researchers. Finally, to recruit, train and pay lay co-researchers in their role. Results The benefits of PPI have included developing ideas which are important to people living with memory loss; support for PPI received from the funders and research ethics committee, high levels of interest from volunteer groups, and lasting enthusiasm from many of the co-researchers. Organisational challenges were met in the requirement for research passports and with payment methods for the co-researchers. Training was beneficial but incurred extra costs for repeated training days. Discussion Overall the benefits outweighed the challenges which were overcome to varying degrees. The lay co-researchers gained membership of a study group and a beneficial partnership developed with the third sector. The biggest challenge was in overcoming the differences in approach to lay co-researchers between NHS Trusts. Organisational culture has been slow to incorporate PPI and this has not yet been fully addressed. It has the potential to delay the start of projects, affect recruitment time, incur extra research costs and disadvantage PPI. Conclusion Buy-in to service user involvement in research studies could be improved by clarifying the requirements for NHS Trust approval and by simplifying the system for financial reimbursement to lay co-researchers. This would improve inclusivity and provide a smoother process for the research team and the co-researchers.